You are on page 1of 15

# 1

1. ()(Function):

-->
(Dependent variable number)
--> (Variable number)
:
y(x) = f(x) = x 2

x --->, ,(0,10)
y --->, , (0,100)
f(x) --->

x2

x=2ty=4
1 to
1()3
2,3,4!
!

xy11(one
to one)yx1
1(y=0x3)
{ y | 3 y 2}
2. (Inverse function):
!!
:

y(x) = x 2 d x(y) = y
: :

f(x) = y d f 1 (y) = x
:

sin  = y d sin 1 y = 
:

f(f 1 (y)) = y
: sin sin 1 y = y,sin 1 sin =

3.

(1).
I, (Trigonometric function)

(I).

(, )

(, )

cos  =

x
x 2 +y 2

(, )

tan  =

y
x

(, )

cot  =

x
y

(, )

csc  =

1
sin 

(, )
:

y
sin  = x 2 +y 2

sec  =

[1, 1]
[1, 1]

(, )

(, )

( , 1] [1, )
( , 1] [1, )

1
cos 

( , 1] < x 1

(II)

(III).

(A).
sin 2 + cos 2 = 1

sec 2 tan 2 = 1

csc 2 cot 2 = 1

(B).

## sin 2 = 2 sin  cos 

, cos 2 = 2 cos 2  1

(C).

sin

cos

(D).
+



## sin  + sin  = 2 sin 2 cos 2

+

cos  + cos  = 2 cos 2 cos 2
II,
(I).

[1, 1]

sin 1 

[1, 1]

cos 1 

2 , 2

[0, ]

(, )

tan 1 

2 , 2

(, )

cot 1 

2 , 2

(, 1] [1, )

sec 1 

, 2 0, 2

(, 1] [1, )

, 2 0, 2

csc 1 

(II).

sec1

cos 1

tan 1

cot 1

sec 1

csc1

(2).
I.(Exponential function)

y ( x) = a x , a > 0, a 1
, a (Base)x (Exponent)
(I).

a >1

0 < a <1

( , )

[0, )

y ( x) = e x

e=2.71828

(II).:

e x e y = e x+y
(e x ) y = e xy
ex > x
ex > 0

(0, )

y ( x) = log a

(, )

, a (a > 0)

(I).

a >1

a <1

## : e (Natural exponential number)

(II).:
ln(xy) = ln x + ln y
ln( xy ) = ln x ln y
ln
ln x r = r ln x
log b x = lnln bx
e x > x > ln x

(3).
I. (Power function)

y ( x) = x a

## II. (Polynomial function)

,:

y ( x) = an x n + an1 x n1 + ... + a1 x + ao
n

= ai x i
i =0

ai , i i n

: y ( x) = 3 x 3 + x + 3 3
:

y ( x) = ax 2 + bx + c
b
c
= a( x 2 + x + )
a
a
b
b2 c b2
2
= a( x + x + 2 + 2 )
4a
a
a 4a
2

b
c b
= a ( x + )2 + 2
a
a 4a

b 2 4ac b 2
= a ( x + ) +
a
4a 2

: y ( x) = x 2 + 3 x + 5
: y ( x) = x 2 + 3 x + 5
2

3
9

= x+ +5
2
4

2
3 11

=x+ +
2
4

(4).
I.(Hyperbolic function)

(I).
sinh x =

e x e x
2 , cosh x

e x +e x
2

tanh x =

sinh x
cosh x , coth x

cosh x
sinh x

sec hx =

1
cosh x , csc hx

1
sinh x

10

(II).

sinh x

cosh x

tanh x

coth x

sec hx

csc hx

11

(III).:

cosh 2 x sinh 2 x = 1
tanh 2 x + sech 2 x = 1
coth 2 x csch 2 x = 1

I.
(I).

( , )

sinh 1 x = ln
ln(x + x 2 + 1 )

[1, )

cosh 1 x = ln
ln(x + x 2 1 )

[0, )

(1,1)

1 1+ x
tanh 1 x = ln

2 1 x

( , )

cot h 1 x = ln
ln( x+1
x1 )

( , ) y 0

( , 1) (1, )

1+ 1x 2
x

( 0,1]

sec h 1 x = ln
ln(

( , ) x 0

csc h 1 x = ln
ln( 1x +

12

1+x 2
x

( , )

[0, )

( , ) x 0

(II).

sinh 1 x

:
:

cosh 1 x

tanh 1 x

coth 1 x

sech 1 x

csch 1 x

sinh 1 x
y = sinh 1 x ,

e y e y
sinh y = x =
2
13

e 2 y 2 xe y 1 = 0

e y = x 1 + x2
e y > 0, x > 0

e y = x + 1 + x2

y = ln x + 1 + x 2

4.

## (f ! g)(x) = f(x) ! g(x)

f(x)
( gf )(x) = g(x)
f ) g(x) = f(g(x))
f
: f ( x) = x + 1, g ( x) = x 2 , ( f + g )( x),( f g )( x),( f i g )( x),( )( x)
g
: ( f + g )( x) = ( x + 1) + x 2 = x 2 + x + 1
( f i g )( x) = ( x + 1)i x 2 = x3 + x 2
f
x +1
( )( x) = 2
g
x
5. :
(1). ()
x=5,
x>3, 3,3
3,3
xm3

x m3
x <3

,dxm3
,dx<3

and x[ 3
and x>3 d 3 < x < 3

14

Note:

x if x m 0
x =
x if x<0

xa <b

(2). ()
x+y=5,
x+y>5, x+y=5,

x2 +y2 =5

, ()

x2 +y2 m5

, ()

(3). ()
x+y+z=5,
x+y+z>5, x+y+z=5

:,

15